Marvin & James save the day! and Elaine helps! - Broach, Elise (Broach, Elise. Masterpiece adventures, 2019)
Karl and Christina are getting married! James feels happy for his father. Karl asks James to be the ring bearer. James is excited to attend the wedding... but also very nervous. While he loves Christina, he is worried about losing his dad to a different family. And what if, at the ceremony, James drops the ring? His best friend Marvin promises to help him, but Marvin ends up with an even more important job when something goes terribly wrong. Will the wedding be ruined?